PENERAPAN METODE SQ4R DALAM MENINGKATKAN KEMAMPUAN MEMBACA INTENSIF PADA SISWA KELAS IV SD INPRES KALUKUBULA - Azrah, Azrah (BAHASANTODEA, 2016)
The objective of this research is to describe the application of SQ4R Strategy in reading intensive and to improve reading intensive skill at fourth grade students of SD Inpres Kalukubula. Kind of this research classroom action research which implemented at fourth grade student of SD Inpres Kalukubula. This research is adopting a model whish developed by Kemmis through classroom action research planning which implemented by a cycle that is planning, implementing, observation, and reflection. Basd on the result of this research, it is known that SQ4R Method can improve at the fourth grade srudents of SD Inpres Kalukubula in reading intensive. The Result obtained at the cycle 1 that is in the sentence logical aspect of cycle 1 is 33,33% and there is in the cycle II is 85,71%. Accuracy aspect of main sentence which found at the cycle I is 57,14 and cycle II is 90,47%. Aspect of sequence sentence in the paragraph at the cycle I is 42,85 a nd in the cycle II is 85,71%. Aspect of compability sentence with the content of the text at the cycle I is 61,90% and in the cycle II is 85,71%. The comparison of the test result at the cycle I and cycle II can be seen is enough significance, except at the logical unsure of sentence. There is an improvement at the result of the student learning at fourth grade student of SD Inpres Kalukubula had done reading of intensive learning with using SQ4R method with the theme â€œ visiting an orphanageâ€ at the cycle I and the theme â€œ school coperationâ€ at the cycle II. The students completeness percentage in intensive reading in cycle I achieve 19,04%, with the average score is 69Â  and less from the standard of completeness which decided that is 70. At the cycle Ii the percentage comleteness happen an improvement tobe 76,19% with the average score is 83,9 and it had complete standard of completeness which decided. The improvement which happen can be seen from the result which obtained that is the percentage is too improve from cycle I to the cycle II.